COD REMOVAL OF PARBOILIZED RICE WASTEWATER BY CYANOBACTERIA APHANOTHECE MICROSCOPICA NÄGELI / REMOÇÃO DE DQO DO EFLUENTE DA PARBOILIZAÇÃO DO ARROZ PELA CIANOBACTÉRIA APHANOTHECE MICROSCOPICA NÄGELI - BASTOS, REINALDO G.; QUEIROZ, M. I.; ZEPKA, L. Q.; VOLPATO, G.; GARCIA, M. S.; JACOB-LOPES, E. (Revista Brasileira de Engenharia de Biossistemas, 2009)
Cyanobacteria are photosynthetic prokaryotes organisms used on single-cell protein production and wastewater treatment for nitrogen and phosphorus removal. Moreover, some strains have the particular characteristic of growing in the dark on simple molecules such as acetate, glucose and organic acids, and consequently reduction of Chemical Oxygen Demand (COD) from nutrient medium. Aphanothece microscopica Nägeli is a cyanobacteria frequently found in south of Brazil, which has been studied with respect to residues valorization in the single-cell protein production. Wastewater from rice parboilization process presents characteristics that suggest the removal of nutrients and organic matter by incorporation into a biomass. The aim of this paper is to extend the findings of the previous studies about heterotrophic metabolism application of these cyanobacteria on wastewater treatment, considering influence of temperature and inoculum amount. Experiments indicated that Aphanothece microscopica Nägeli presented high potential of organic matter removal from parboilized rice effluent by 300 mgL-1 inoculum at temperature range 25-35oC.